Marketing Management Development for Training Improvement English Learning “Conversation Club” - Indahwati Indahwati; Ruswiati Suryasaputra; Lusy Tunik Muharlisiani (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this research is to find out how to manage marketing, increase the quantity of the “Conversation Club” learning training. Design/methodology/approach: This research approach is quantitative. The method used is observation, interviews, and documentation. Findings: The result of this research is marketing management training: conversation club neighborhood MSMEs using the marketing mix. The proposed model 1) establishes a correspondence network by utilizing WhatsApp bunches starting from the RT to the city level, 2) framing discussion clubs by collaborating with educational organizations, and 3) collaborating. with environmental MSMEs as a commercial center (marketplace). Gap Research in products: trainees create a generation of quality and achievers. Price: using the concept of the magnitude of the conclusion. Place: neighborhood MSMEs that can be applied in Surabaya or in-house training. Promotion: promoting the establishment and cooperation with environmental MSMEs as a commercial center (marketplace) and marketing by conducting socialization to stakeholders. Research limitations/implications: Data innovation time is a test for the public, have not been able to take advantage of this change due to the limited English language, especially for young people which is useful. Practical implications: The motivation behind this exploration is to identify the English learning model as a discussion club in Karang Taruna which will also serve as a commercial center (market) for the neighborhood MSMEs as a commercial center (market), and will serve as a pilot project for all Karang Taruna in Indonesia. Originality/value: This Paper is original Paper type: Research paper